Autofluorescence of condensed heme aggregates in malaria pigment and its synthetic equivalent hematin anhydride (beta-hematin) - Bellemare, Marie-Josée; Bohle, D Scott; Brosseau, Colin-Nadeau; Georges, Elias; Godbout, Marianne; Kelly, Jane; Leimanis, Mara L; Leonelli, Richard; Olivier, Martin; Smilkstein, Martin (The journal of physical chemistry. B, 2009)
The condensed crystalline phase of iron(III) protoporphyrin IX either isolated from parasite culture as malaria pigment (hemozoin) or synthetic equivalent hematin anhydride exhibits a solid-state autofluorescence characterized by an excitation maximum of 555 nm and an emission maximum of 577 nm. The excitation spectrum maximum at 555 nm corresponds to the Q(0,0) band in the absorption spectrum which represents the lowest singlet of the material. This suggests that the fluorescent emission is due to the heme condensed phase. The photoluminescence lifetime of tau(f) = 2.7 +/- 0.8 ns as measured at four wavelengths between 550 and 600 nm is in the range of Frankel exciton in porphyrinic condensed phases. The material is shown to have an optical band gap of 2.04 eV characteristic of a semiconductor. Luminescence is markedly dependent upon the degree of hydration and the emission does not seem to be caused by presence of zinc(II) protoporphyrin IX or free-base protoporphyrin IX in the lattice. The autofluorescence can be used for in vivo tracking of hemozoin, for determination of parasitemia levels, and for infection monitoring and possibly for drug screening studies.